Maxillary sinus lesions and their association with apical lesions observed by cone beam computed tomography. A retrospective cross-sectional study - Rodríguez López, Manuela Alejandra (2023)
Introduction: Through cone beam computed tomography, alterations in the maxillary sinuses, such as opacities, space occupation and thickening of the mucosa, can be observed. Some factors contribute to this thickening, standing out among dental factors, periodontitis, apical pathology and endodontic treatments. Objective: To evaluate the association between changes observed in the maxillary sinuses and apical lesions using cone beam computed tomography. Materials and methods: It was a descriptive study with a retrospective and cross-sectional, correlational, field, non-experimental design. The sample consisted of 115 tomographic volumes obtained using Planmeca ProMax 3D Classic equipment (Planmeca, Helsinki, Finland). The presence/absence of endodontic treatment in the present posterior teeth, presence/absence of periapical lesion associated with these teeth, the size of the periapical lesion, presence/absence of alteration in the maxillary sinus and its thickness were evaluated. Results: Apical lesions were observed that averaged a size of 3.32 ± 1.82 mm, and almost half (44.35%) presented between 2 and 4 mm in size. The main alteration of the maxillary sinus that was observed was the thickening of the mucosa (58.26%). The average thickness of the thickening of the sinus mucosa was 3.51 ± 1.78 mm, with 72.17% of the cases with thickening greater than 2 mm. Conclusion: There was an association between the changes observed in the maxillary sinuses and apical lesions. The larger and closer the lesion was to the sinus, the greater the thickening of the sinus mucosa.